The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4319/lo.2009.54.2.0571
|View full text |Cite
|
Sign up to set email alerts
|

No limit? The multiphasic uptake of silicic acid by benthic diatoms

Abstract: Silicic-acid uptake kinetics for a field population of benthic diatoms were examined using a radioisotope tracer over a concentration range of 0-300 mmol L 21 . The microphytobenthos half saturation constant (54 mmol L 21 ) and specific uptake rates (0.096 h 21 ) for silicic acid were well above those usually found in the pelagic environment. Silicic-acid kinetics were hyperbolic only at low concentrations (,60 mmol L 21 ). At higher concentrations, a second mechanism that did not suggest saturation was activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Studies of nitrate uptake kinetics of phytoplankton have demonstrated a phase transition point at approximately the same concentration (60 μmol l -1 ) as that in the present study (Lomas & Glibert 1999b, Collos et al 2005. Our previous work also revealed a similar mechanism during silicic acid uptake by the MPB at high concentrations (Leynaert et al 2009). However, to our knowledge, there is little evidence for a similar process for ammonium.…”
Section: Ammonium and Nitrate Uptake By Mpbmentioning
confidence: 50%
See 2 more Smart Citations
“…Studies of nitrate uptake kinetics of phytoplankton have demonstrated a phase transition point at approximately the same concentration (60 μmol l -1 ) as that in the present study (Lomas & Glibert 1999b, Collos et al 2005. Our previous work also revealed a similar mechanism during silicic acid uptake by the MPB at high concentrations (Leynaert et al 2009). However, to our knowledge, there is little evidence for a similar process for ammonium.…”
Section: Ammonium and Nitrate Uptake By Mpbmentioning
confidence: 50%
“…primary production (Underwood & Kromkamp 1999, Serôdio & Catarino 2000, vertical migration in intertidal (Palmer & Round 1965, Underwood et al 2005 and subtidal regions (Ní Longphuirt et al 2006), and their resuspension during tidal flooding (Lucas et al 2000). However, despite the extensive literature available, very little experimentation has been carried out on the direct uptake of dissolved inorganic nutrients by in situ populations (Thornton et al 1999, Leynaert et al 2009), a process which is routinely represented in modelling and nutrient budget studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The silica concentration of diatom cells depended on the cell size and larger cells have more silica than smaller ones (Falasco et al, 2009). Leynaert et al (2009) observed that small size phytoplankton tended to dominate in nutrient-poor water columns, whereas large size phytoplankton dominated in nutrient-rich regions. Martin-Jézéquel et al (2000) found that silicification of diatoms can be influenced by light which improves Si uptake by promoting phytoplankton growth (Xu et al, 2009).…”
Section: )mentioning
confidence: 98%
“…Si concentrations were determined according to Strickland and Parsons (1968). The maximal uptake rate (V m ) and the half saturation constant (K m ) were determined by fitting the MichaelisMenten equation (De La Rocha et al, 2000;Bhattacharyya and Volcani, 1980;Leynaert et al, 2009) to the experimental results. The uptake rate (V) was determined by the disappearance of nutrient concentration in each subculture (Eq.…”
Section: Nutrient Uptakementioning
confidence: 99%